The kingdom of dogs: Understanding Pavlov's experiments as human–animal relationships. (February 2020) - Adams, Matthew
The growth of Human–Animal Studies, multi-species, and posthuman scholarship reflects an "animal turn" offering important theoretical, ethical, and methodological challenges to humanities, science, and social science disciplines, though psychology, in particular, has been slow to engage with these developments. This article is the first to apply the conceptual lens of the "animal turn" to Pavlov's experiments with dogs. It is unique in applying in particular the work of feminist cultural theorist Donna Haraway, to radically reframe the human–animal relationship at the core of these landmark experiments. This original portrait is contrasted with contemporary retellings of those experiments which ignore or are indifferent to the complexities of that relationship. Paying attention to nonhuman others that constitute animal experimentation in psychology, historically, today, and in retellings, is argued to be a vitally important step for psychology today. The analysis provided constitutes a distinctive, radical shift in the way psychology might approach the lives of nonhuman animals, in its own past and present, with far-reaching implications for the future development of psychology.